Eastern Orthodox Christianity the Essential Texts - Geffert, Bryn 1967-; Stavrou, Theofanis G. 1934- (Yale University Press, 2016)
An essential, one-of-a-kind reader, this book frames, explores, and interprets Eastern Orthodoxy through primary sources. It is the first comprehensive reader on the Eastern Orthodox Church for the English-speaking world and is accessible to readers with no prior knowledge of theology or religious history. Lively introductions and short narratives touch on anthropology, art, law, literature, music, politics, women's studies, and a host of other areas. These texts are brought together to survey the fascinating history of the Eastern Orthodox Christian tradition--From back cover